First cases of European bat lyssavirus type 1 in Iberian serotine bats: Implications for the molecular epidemiology of bat rabies in Europe. - Patricia Mingo-Casas; Virginia Sandonís; Elena Obón; José M Berciano; Sonia Vázquez-Morón; Javier Juste; Juan E Echevarría (Public Library of Science (PLoS), 2018)
Previous studies have shown that EBLV-1 strains exclusively hosted by Eptesicus isabellinus bats in the Iberian Peninsula cluster in a specific monophyletic group that is related to the EBLV-1b lineage found in the rest of Europe. More recently, enhanced passive surveillance has allowed the detection of the first EBLV-1 strains associated to Eptesicus serotinus south of the Pyrenees. The aim of this study is the reconstruction of the EBLV-1 phylogeny and phylodynamics in the Iberian Peninsula in the context of the European continent. We have sequenced 23 EBLV-1 strains detected on nine E. serotinus and 14 E. isabellinus. Phylogenetic analyses were performed on the first 400-bp-5' fragment of the Nucleoprotein (N) gene together with other 162 sequences from Europe. Besides, fragments of the variable region of the phosphoprotein (P) gene and the glycoprotein-polymerase (G-L) intergenic region were studied on Spanish samples. Phylogenies show that two of the new EBLV-1a strains from Iberian E. serotinus clustered together with French strains from the North of the Pyrenees, suggesting a recent expansion southwards of this subtype. The remaining seven Iberian strains from E. serotinus grouped, instead, within the cluster linked, so far, to E. isabellinus, indicating that spatial distribution prevails over species specificity in explaining rabies distribution and supporting interspecific transmission. The structure found within the Iberian Peninsula for EBLV-1b is in concordance with that described previously for E. isabellinus. Finally, we have found that the current EBLV-1 European strains could have emerged only 175 years ago according to our evolutionary dynamics analyses.